1997
DOI: 10.1021/op970107f
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Palladium from Organic Reaction Mixtures by Trimercaptotriazine

Abstract: In an effort to remove residual palladium from a drug candidate prepared by palladium-catalyzed indolization, many treatments were examined. The most effective treatment was to precipitate palladium from solution using 2,4,6-trimercapto-s-triazine (TMT), which reduced palladium levels from 600−650 ppm to 20−60 ppm in an isolated indole intermediate. Subsequent crystallizations routinely afforded active pharmaceutical ingredient with <1 ppm of palladium. TMT treatment should prove useful to reduce the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 18 publications
0
90
0
Order By: Relevance
“…[10] This treatment resulted in insoluble complexes of TMT and Pd which could be filtered out of the product solution. [11] The original synthesis called for the drug substance to be prepared by a palladiumcatalyzed indolization.…”
Section: Solid Tmtmentioning
confidence: 99%
“…[10] This treatment resulted in insoluble complexes of TMT and Pd which could be filtered out of the product solution. [11] The original synthesis called for the drug substance to be prepared by a palladiumcatalyzed indolization.…”
Section: Solid Tmtmentioning
confidence: 99%
“…Since this approach had been successful with various, closely related intermediates, initial work was focused on the use of insoluble scavenger materials to remove the metal from a solution of the API. One of the most effective commercially available treatments is thiolcontaining reagents on solid supports [2]. Therefore, our first attempt utilized in-house prepared 10% wt./wt.…”
Section: Resultsmentioning
confidence: 99%
“…These approaches can be divided into two main categories (Scheme 2): (A) solid phase and precipitation treatments (API in solution) and (B) extraction treatments (API in the precipitate) [2,3]. Although approach A is normally the most common, it did not work in a practical way for our example, and therefore, a comprehensive screen of chelating agents was carried out to explore the unusual alternative B.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 119 Sn MAS-NMR experiments revealed that the regeneration of 2 was incomplete in cycles 3, 4 and 5 and presumably due to a partial removal of the palladium residues along the cycles. On the other hand, we were delighted to see that treatment of polymer 5 with a THF solution of 2,4,6-trimercapto-s-triazine (L 2 ) [60,61], followed by a reaction with 2 equiv. of PhMgBr allowed both the regeneration and recycling of polymer 2 at least 4 times (Fig.…”
Section: Recycling Experimentsmentioning
confidence: 99%